IN VITRO BEHAVIOUR OF PLASMODIUM FALCIPARUM STRAINS BY ALKALOIDS AND TANNINS EXTRACTED FROM ROOT OF MITRAGYNA INERMIS, A MEDICINAL PLANT - Serge, Kumulungui Brice; Serges, Ondo-azi Alain; Ludovic, Mewono; Elvis, Otogo N’nang; Bernardin, Akagah; Francis, Fumoux; Alfred, TraorÉ (International Journal of Current Pharmaceutical Research, 2015)
Mitragyna inermis (Willd.) O. Ktze, is a plant belonging to the Rubiaceae family. It is used in West Africa by traditional healers for treatment of accesses febrile generally bound to access malaria, but also to treat several other pathologies. We have collected a medicinal plant, Mitragyna inermis root, currently used for malaria treatment in Burkina-Faso. After extracted Alkaloids and Tannins, the in vitro culture of Plasmodium falciparum strain isolated from infected patients showed that the alkaloids extracts presented an excellent antiplasmodial activity on P. falciparum strain (IC50 = 2.36 and 2.56 µg/ml respectively) after 24 and 48h of incubation at 37 °C. On the other hand, the tannins extracts no presented antiplasmodial activity (IC50>100 µg/ml) but presented an important maturity of P. falciparum strains, letting foretell a possible use of the polyphenolic compounds by P. falciparum as a source of cellular carbon and energy. These results although exploratory are of a fundamental importance for the research in biochemistry and medicine for find new antimalarial prototypes. Keywords: Mitragyna inermis, Malaria, Roots, Tannins, Alkaloids, Plasmodium falciparum.